Model of Education Program Value Increase - A. V. Garmonova; N. A. Ryakhina; E. E. Sokolova (Высшее образование в России)
The article describes the experience of the private further professional education establishment in integration with private medical organizations as a hi-tech clinic base. The purpose of the experience was to work out an education program of professional retraining which enables medical organization to extend the range of its services. The demand for such programs investment stems from the gap between the professional level of medical workers training at universities and the needs of hi-tech segment of cosmetology service which requires highly qualified specialists.The gap between the increasingly changing market demands and the existing higher education offer may be bridged through involvement of practicing professionals in education process.The authors consider the best Russian and foreign practices of interaction between private medical establishments and private education establishments aimed at creation Centers of Excellence on the example of Neo Clinic Tuymen. The presented model shows the competitive advantages of a professional retraining education program characterized by a big concentration of resources per student and a high value of education service. The article may be useful for the university management in Russia in developing and updating strategies and programs of practice-oriented education that will meet the requirements of regional labour markets, concrete organizations and employers and contribute to graduates’ adaptation to actual production process.